Alternaria alternata causing foliar blight on Chrysanthemum morifolium in Corrientes, Argentina - Patricia, Gauna Mónica (2020)
In Corrientes, province of Argentina, Chrysanthemum morifolium Ramat (Asteraceae), is the second most important crop of cut flowers, following gladiolus. Chrysanthemum is a type of floral plants frequently affected by several diseases such as white rust (Puccinia horiana), withering (Fusarium sp. and Verticillium sp.), spots and foliar blight caused by Alternaria spp. and Septoria sp. (1). In Corrientes Province, this disease produces losses of 60% plants in greenhouses. Thus, new observations and studies have been conducted to get to know the species of Alternaria that is involved in the disease affecting chrysanthemum in Corrientes. Samples showing symptoms of foliar blight were collected from crops in Concepción and Corrientes Cities at different times of the year during the growing period...